Equivalent Resilient Modulus Inversion and Calculation of Different Asphalt Pavement Structures. (22nd November 2021) - Cao, Mingming; Huang, Wanqing; Zou, Yiwen; Wu, Zhiyong
Abstract : Based on the modulus inversion theory and the equivalent principle of deflection basin, by analyzing the deflection basin data of each structure layer measured by the FWD, the obtained equivalent resilient moduli of different structural layers in three different structures (a semirigid type Asphalt pavement and two inverted asphalt pavements) were compared. At the same time, the calculated equivalent resilient modulus of the top surface of the structural layer based on the inversion method was used to modify the existing theory formula. The results show that, with the inversion method and the theoretical calculation method, the calculated equivalent resilient modulus of the top surface of the cushion layer has a small error, but the theoretical calculation method overestimates the equivalent resilient modulus of the top surface of the cement stabilized crushed stone layer and the top surface of the graded crushed stone transition layer, especially for the inverted asphalt pavement; by contrast, the corresponding result of the inversion method is closer to the value in actual engineering. While determining the equivalent resilient modulus of the cushion layer, the influence of the thickness of the cement stabilized crushed stone layer needs to be considered, and the inverted asphalt pavement structure should adopt a thicker asphalt layer to reduce the modulus deviation; at the same time, the more the structural layers and the larger the difference in the interlayer modulus ratio, the larger the deviation of equivalent resilient modulus of the top surface of the base layer; for the inverted asphalt pavement and semirigid asphalt pavement, the correction coefficients of the calculation formula of the equivalent resilient modulus of the top surface of cement stabilized gravel layer are 0.35∼0.55 and 0.65∼0.75, respectively. The inversion method can be used to determine the equivalent resilient modulus of each structural layer of the inverted asphalt pavement and semirigid asphalt pavement, and its results can provide a basis for the design of the structure reconstruction of asphalt pavement.